INTEGRATING A COMIC MAKER SITE AS AN ALTERNATIVE EDUCATIONAL TECHNOLOGY IN INDONESIAN EFL CLASSROOM - Akiko Rahmawati (JELLT (Journal of English Language and Language Teaching), 2022)
Abstracts Using latest technology as a teaching strategy, teacher could create a captivating classroom where students’ motivation can be grasped. As an attempt of fulfilling students’ needs of real-world education, MALL is explored. Pixton, the digital comic maker is the highlighted resource in this research. The purpose of this research is to investigate the advantages and challenges of changing the comic strips resources from conventional to digital for teaching writing comprehension in higher education. By applying (PjBL) as the framework of creating research cycles, content analysis and qualitative study are used to evaluate the use of Pixton. The advantage of using Pixton in higher education is to encourage students’ autonomous learning’s skills such as learning to learn, critical thinking, and collaboration. In other hands the challenges divided into technical and non technical area. This study definitely answers the questions regarding the advantages and challenges of applying Pixton in higher education. Keywords: Mobile Assisted Language Learning, Project Based Learning, higher education, Pixton, Comic strips Abstraksi Menggunakan teknologi terkini sebagai strategi pembelajaran, guru dapat menciptakan kelas yang menarik dimana motivasi siswa dapat diraih. Sebagai upaya untuk memenuhi kebutuhan siswa akan pendidikan berbasis real-world, MALL digunakan. Pixton, sarana membuat komik digital sebagai sumber utama dalam penelitian ini. Tujuan penelitian ini adalah untuk menemukan manfaat dan tantangan dalam perubahan sumber komik strip konvensional menjadi digital untuk mengajar menulis di perguruan tinggi. PjBL digunakan sebagai landasan dalam pembuatan siklus penelitian, konten analisis dan kualitatif digunakan untuk mengevaluasi penggunaan Pixton. Manfaat menggunakan Pixton di perguruan tinggi adalah untuk mendorong siswa untuk memiliki kemampuan “autonomous learning”, antara lain kemampuan menentukan strategi belajar, berpikir kritis dan kolaboratif. Di sisi lain, ada tantangan yang terbagi menjadi tantangan bersifat teknis dan non teknis. Penelitian ini menjawab pertanyaan berkaitan dengan manfaat dan tantangan menggunakan Pixton di perguruan tinggi. Kata Kunci: Mobile Assisted Language Learning, Pembelajaran Berbasis Proyek, Pixton, komik strip